Simple analysis method for fatty acids in food samples - Maeda, Y. (Shizuoka-ken. Inst. of Public Health and Environmental Science (Japan)); Ochi, S; Yamamoto, M; Masui, T; Matsubara, S (Food Hygiene and Safety Science (Shokuhin Eiseigaku Zasshi), 1987)
A simple and rapid analytical method for the determination of fatty acids in food samples by gas liquid chromatography (GC) was developed A sample of 10mg (as lipids) was dissolved in 2ml of hexane containing triphenylethylene as an internal standard (IS). Then 1ml of 2N sodium hydroxide-methanol solution was added, and the mixture was heated at 60° in a water-bath for 1min. Methyl-esterification was carried out with 1ml of 2N hydrochloric acid-methanol solution. The hexane layer was rinsed with water, and the fatty acid composition of food samples was estimated by GC on a Unisole 3000 column. Total fatty acids were determined from palmitic acid (16:0) composition and the peak area ratio of 16:0 methyl ester and IS. The proposed method was applied to mixed lipids and lipids extracted from food, and the results were compared with those obtained by the sodium methoxide (NaOMe) method and BF3 methanol (BF3-MeOH) method. The proposed method was superior to the NaOMe method and BF3-MeOH method in terms of detection limit and reproducibility. This method allows the rapid preparation of fatty acid methylesters and the simple and accurate determination of fatty acids, and is suitable for the routine analysis of fatty acids in food samples.